Ultra‐narrow band blue emission of Eu2+ in halogenated (Alumino)borate systems based on high lattice symmetry. Issue 5 (16th October 2018) - Wei, Yi; Qu, Xingyu; Li, Guogang; Cheng, Ziyong; Molokeev, Maxim S.; Lin, Chun Che; Chan, Ting‐shan; Chang, Chung‐Kai; Chuang, Yu‐Chun; Lin, Jun
Abstract: Phosphor materials with ultra‐high color purity are highly desired in backlit display and WLEDs. How to achieve high‐purity three‐primary emission in rare earth ions activated inorganic phosphors has become a hot topic. Herein, we reported ultra‐narrow band and highly efficient blue‐violet‐emitting Eu 2+ ‐doped Ba2 B5 O9 X (fwhm = 31 nm) and NaBa4 (AlB4 O9 )2 X3 (X = Cl, Br) (fwhm = 43 nm) phosphors with peak positions around 424‐437 nm. Especially, the color purity of Ba2 B5 O9 Cl:Eu sample even exceeded 97%, its internal quantum efficiency could achieve 87%. The EXANES analysis revealed that the Eu mainly existed in the form of +2. According to the Rietveld structural refinement, extraordinarily narrow band emission should be attributed to the highly symmetric lattice structures with the flower‐like polyhedrons in the studied (alumino)borate matrix. Significantly, the color gamut of as‐prepared blue phosphor combined with the standard green and red phosphors was almost close to that of Rec. 2020 display standard. In addition, cation substitution strategy in NaBa4 (Alx B5‐ x O9 )2 Cl3 ( x = 0‐4) and NaBa4 (Gay B5‐ y O9 )2 Cl3 ( y = 0‐3) samples successfully achieved spectra adjustment, and the underlying mechanism was proposed. All these results demonstrate that the as‐prepared phosphors could be superior blue‐emitting candidates for backlit display as well as WLEDs. Abstract : Ultra‐narrow band blue emission of Eu 2+ (fwhm = 31‐43 nm) are achieved in halogenated (alumino)borate matrixes due to the highly symmetric lattice structures with the flower‐like polyhedrons, of which color gamut could reach the Rec. 2020 display standard by combining the standard green and red phosphors.